Innovation in geographical education: the pedagogy of projects a possibility in the teaching of geography - Luz Neto, Daniel Rodrigues Silva (Geosaberes, 2018)
Geography teachers, in the current context, are being challenged to re-signify their pedagogical practices. In this sense, the objective is to report pedagogical practices in the teaching of Geography in a private educational institution in Taguatinga-Distrito Federal. The action research was adopted, because it is the analysis of the pedagogical practice itself. Having as procedure: observation, photographic record, bibliographic research and production of a report. The pedagogy of the projects was used as a theoretical-methodological possibility in the attempt to make the knowledge significant in the teaching of Geography for the students. Thus, the projects were built through group work, production of didactic material in the classroom, internet research, daily problematization in the construction of concepts and the appropriation of everyday reality with the objective of articulating theoretical and social practices . All this, contribute to the construction of a geographical reasoning in the students of the institution in has acted.